Back to the future: A monastic perspective on corporate governance - Emil Inauen; Katja Rost; Margit Osterloh; Bruno S. Frey (Management Revue, 2010)
The financial crisis is a crisis of governance as well. In search of answers and solutions many scholars and practitioners recommend improved output control, i.e. better external incentives or even stricter regulations. Monasteries demonstrate that alternative models may be more suitable to enhance sustainable governance quality and to reduce agency problems. In the long history of monasteries, some abbots and monks were known to line their own pockets and some monasteries were undisciplined. Monasteries developed special systems to combat these excesses thus ensuring their survival over centuries. We study these features from an economic perspective. Derived from an analysis of the Benedictine monastery of Engelberg we offer three improvements of applied governance designed to reduce agency problems. First, monastic governance emphasizes clan control rather than output control. Monasteries demonstrate that organizations can prevent agency problems by complementing external discipline with internal behavioral incentives, such as value systems and voice. Second, organization members making firm-specific investments are motivated by broad participation rights and co-determination. Third, the Benedictines are able to apply supportive external control mechanisms, which are not perceived as controlling.
Keywords: 650; corporate governance; financial crisis; psychological economics; monasteries; principal agency theory; Benedictine Order